Importance of squatting and sitting on the floor: perspectives and priorities of rural Indian patients with stroke. Issue 4 (6th June 2016) - Prakash, V; R Patel, Shrishma; Hariohm, K; S Soni, Vandita; Alagumoorthi, G
Abstract: Background: Identifying activities that are preferred and valued by patients' is essential to optimize rehabilitation outcomes and quality of care in stroke rehabilitation. Deep knee flexion (DKF) activities like squatting and sitting on the floor are regularly performed and preferred daily activities in many cultures. Yet few studies have investigated its importance as perceived by patients with stroke. Objectives: To identify the magnitude of importance of squatting and sitting on the floor in carrying out daily activities in adults diagnosed with stroke. Methods: We conducted a survey among patients with stroke using a questionnaire. A sample of convenience of 123 patients diagnosed with stroke who were receiving physiotherapy in rural rehabilitation setting in Gujarat, India participated. All patients were asked to rate the importance of DKF activities in performing various daily activities related to self care, mobility, domestic life, work and community participation. Results: Sixty-eight percent of participants rated DKF activities as very important for carrying out their daily activities. Toileting (78%), bathing (68%), eating (68%), praying (54%) and work (51%) were the activities for which DKF activities were rated as very important by both men and women. However, higher proportion of women compared to men rated domestic life activities such as cooking, washing cloths and cleaning house as very important. Conclusions: Because a substantial proportion of patients with stroke identified DKF activities as very important for performing major daily activities, independent performance of squatting and sitting on the floor should be considered as one of the important rehabilitation goals for patients with stroke.